Contested local power in influencing regional development planning in Nabire Papua, Indonesia - Lewerissa, Ch. M.; Edyanto, Edyanto (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This study analyzes the relationship dynamics between local government bureaucratic elites and political elites in Nabire Regency, Papua Province, using a quantitative approach with observation and questionnaires. The research reveals that the Regional Development Planning Agency (Bappeda) contributes significantly (83.1%) to the development planning process, indicating a strong technocratic influence. However, Bappeda faces challenges including unprofessional human resource management, limited budget and infrastructure, poor administrative organization, and inadequate planning and implementation of community-focused development programs. Local elites also exert a significant positive influence (78.7%) on the development planning process. Their role is characterized by the politicization of special autonomy, representation politics concerning poverty and resource management, Papuanization politics focusing on local empowerment, and the coastal-highlands dichotomy affecting development distribution. The study highlights the complex interplay between bureaucratic efficiency and local political dynamics in shaping regional development. It underscores the need for improved resource management, better administrative practices, and more inclusive planning processes. The findings also emphasize the importance of addressing political issues such as special autonomy, representation, and regional divisions to ensure equitable and effective development in Nabire Regency.